Notes on gastric cancer - Carrillo Maurtua, Luis (1952)
Not only the interest - very desirable in the surgeon - to maneuver in unfamiliar fields and anatomical long inspired him fearful and cautious respect, which has prompted some to take the scalpel nerve abdomen neurovascular crossroads in which was a simple approach and boldness.